IMPLEMENTASI MODEL PEMBELAJARAN PADA OLAHRAGA PERMAINAN BOLA TANGAN PADA SISWA TINGKAT SMP 3 PRAYA KECAMATAN PRAYA LOMBOK TENGAH NTB - Fery Syahrial; Fatimah Fatimah (LPPM Institut Pendidikan Nusantara Global, 2020)
Peer teaching is a learning model that can develop affective aspects such as collaboration, communication and develop self-confidence so that the amount of active learning time of students can increase. This study aims to identify an increase in the amount of Active Learning Time in learning maturity by applying the Peel Teaching learning model. The method uses Classroom Action Research (CAR), in the SMP 3 Praya Kecamatan Praya High School, with a sample of 33 people and consisted of 14 male studens and 19 female students. The results of the study generally showed students were actively moving, thereby increasing the amount of Active Learning Time which was shown from high motivation when involved in learning the maturity game. Tutors and students can improve their ability to communicate and interact with others. The conclusion of the study is that the peer teaching model can be used in learning maturity, because it can gradually increase the value of collaboration, communication, convey information and develop confidence so that the Total Active Learning Time as an indicator that students are actively involved during learning also increases